A Fe / Mg doped and regulated layered lithium-rich cathode material, preparation method and lithium-ion battery

By doping Fe and Mg in the cobalt-free lithium-rich layered cathode material, a multi-element doped lithium-rich layered cathode material was prepared, which solved the problems of low first-circle Coulomb efficiency and capacity, poor voltage attenuation and rate performance of the existing materials, and significantly improved the electrochemical performance of the material.

CN117154086BActive Publication Date: 2025-03-14NANJING UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310947431.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-03-14
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

The existing cobalt-free lithium-rich layered cathode material Li1.2NixMn0.8-xO2 has problems with low efficiency and capacity of the first circle, and poor discharge average voltage attenuation and rate performance.

Method used

By co-doping Fe and Mg on the basis of a cobalt-free lithium-rich layered cathode material with an R-3m space group structure, a multi-element doped lithium-rich layered cathode material Li1.2-xMgxFeyNi0.2Mn0.6-yO2 was prepared, 0

Benefits of technology

The introduction of Fe and Mg stabilizes the structure of the material, improves the rate performance of the material, alleviates the voltage drop, and improves the overall electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117154086B_ABST
    Figure CN117154086B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium battery material preparation, specifically a layered lithium-rich positive electrode material, a preparation method and a lithium-ion battery regulated by Fe / Mg doping. The present invention prepares a multi-element doped lithium-rich layered positive electrode material by co-doping Fe and Mg on the basis of a cobalt-free lithium-rich layered positive electrode material having an R-3m space group structure to partially replace Mn and Li in a transition metal layer. In the positive electrode material prepared by the present invention, the doping of the Fe element can reduce the covalency between the transition metal and oxygen, thereby suppressing the irreversible oxygen loss of the first cycle, and the Mg element replacing lithium can reduce the Li / Ni mixing, and can support the layered structure. The introduction of the two elements Fe and Mg stabilizes the structure of the material, improves the cycle performance and rate performance of the material, and significantly alleviates the voltage drop of LNMO, thereby improving the overall electrochemical performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery material preparation, and in particular to a Fe / Mg-doped and regulated layered lithium-rich positive electrode material, a preparation method and a lithium-ion battery. Background Art

[0002] With the increasing application of lithium-ion batteries, their use fields have expanded from consumer electronics to electric vehicles and then to smart grids. The demand for high-energy-density lithium-ion batteries is becoming increasingly urgent. As an important component of lithium-ion batteries, people have conducted a lot of research on positive electrode materials with good development prospects.

[0003] Combining anionic and cationic redox reactions, layered lithium-rich oxides (LLROs) have emerged as candidate cathode materials for next-generation lithium-ion batteries, but current commercial cathode materials offer low capacity and cobalt-free lithium-rich layered cathode materials. 1.2 Ni x Mn 0.8-x O2 (hereinafter referred to as LNMO) has the advantages of high theoretical specific capacity, environmental friendliness and low cost, but similar to cobalt-containing lithium-rich layered positive electrode materials, it still has problems such as irreversible oxygen release, low first-cycle coulombic efficiency, poor cycle rate performance and rapid voltage decay. Summary of the invention

[0004] The technical problem to be solved by the present invention is that the existing LNMO materials have the problems of low first-cycle coulombic efficiency and capacity, poor average discharge voltage attenuation and poor rate performance.

[0005] The present invention solves the above problems by co-doping Fe and Mg on the basis of a cobalt-free lithium-rich layered positive electrode material (LNMO) with an R-3m space group structure to partially replace Mn and Li in the transition metal layer, respectively, to prepare a multi-element doped lithium-rich layered positive electrode material (MF-LNMO).

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A multi-element doped lithium-rich layered cathode material with the molecular formula: Li 1.2-x Mg x Fe y Ni 0.2 Mn 0.6-y O2,0 <x<0.02,0<y<0.02。

[0008] Preferably, the molecular formula is: Li 1.19 Mg 0.01 Fe 0.01 Ni 0.2 Mn0.59 O2.

[0009] Preferably, the method for preparing the multi-element doped lithium-rich layered positive electrode material comprises the following steps:

[0010] (1) preparing a metal salt solution: weighing lithium oxalate, manganese oxalate, nickel oxalate, iron acetate, and magnesium oxalate according to the molecular formula ratio, mixing and dissolving in water to obtain a metal salt solution;

[0011] (2) preparing a citric acid aqueous solution: weighing citric acid, dissolving it in water, and stirring until it is completely dissolved to obtain a citric acid aqueous solution;

[0012] (3) preparing a sol: adding a metal salt solution dropwise into a citric acid aqueous solution for chelation, and continuously stirring the mixed solution until a sol is formed;

[0013] (4) After the sol is dried, it is calcined to obtain a multi-element doped lithium-rich layered positive electrode material.

[0014] Preferably, the amount of pure water in both step (1) and step (2) is 15 ml, and the mass of lithium oxalate in step (1) is weighed in excess of 5%-15%.

[0015] Preferably, the stirring temperature in step (3) is 70° C.-90° C., and the stirring time is 4-5 h.

[0016] Preferably, the drying temperature in step (4) is 100°C-130°C, and the insulation time is 10-15h.

[0017] Preferably, the calcination treatment in step (4) is performed twice, wherein the temperature of the first calcination is 800°C-1000°C, and the calcination time is 9h-12h; the temperature of the second calcination is 900°C-1200°C, and the calcination time is 14h-18h, and the heating rate of the two calcinations is 3-7°C / min.

[0018] Preferably, the storage conditions of the multi-element doped lithium-rich layered positive electrode material obtained in step (4) are: vacuum storage or storage in an argon glove box.

[0019] A lithium-ion battery positive electrode, the positive electrode comprising the multi-element doped lithium-rich layered positive electrode material.

[0020] A lithium ion battery comprises a battery casing, an electrode group and an electrolyte, wherein the electrode group and the electrolyte are sealed in the battery casing, the electrode group comprises a positive electrode, a diaphragm and a negative electrode, and the lithium ion battery comprises the lithium ion battery positive electrode.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention selects Fe and Mg as two elements for co-doping to regulate the material composition. 3+ With Mn 4+ With similar ionic radius and electronegativity, Fe doping can reduce the covalency between transition metals and oxygen, thereby inhibiting the irreversible oxygen loss in the first cycle; Mg 2+ The radius is close to that of lithium ions, so Mg can replace lithium in both the lithium layer and the transition metal layer. Replacing lithium with Mg can reduce the Li / Ni mixing and support the layered structure.

[0023] The introduction of Fe and Mg stabilizes the structure of the material, improves the rate performance of the material, and significantly alleviates the voltage drop of LNMO, thereby improving the overall electrochemical performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 XRD refined patterns of (a) MF-LNMO and (b) LNMO;

[0025] Figure 2 Scanning electron microscopy images of materials (a) MF-LNMO and (b) LNMO;

[0026] Figure 3 (a) Distribution diagram of Ni, Mn, Mg, and Fe elements in the sample material MF-LNMO; (b) Distribution diagram of Ni and Mn elements in the comparison sample LNMO;

[0027] Figure 4 Cyclic voltammetry curves of (a) MF-LNMO and (b) LNMO in the voltage window of 2-4.8 V and the scan rate of 0.1 mV / s;

[0028] Figure 5 The voltage-specific capacity diagram of the first charge and discharge cycle of (a) MF-LNMO and (b) LNMO materials at a rate of 0.1C;

[0029] Figure 6 (a) The average voltage-cycle number diagram of 150 cycles and (b) the discharge specific capacity-cycle number diagram of 160 cycles for MF-LNMO and LNMO cathode materials at 1C in the voltage range of 2-4.8V.

[0030] Figure 7 The specific capacity-cycle number diagram of (a) MF-LNMO and (b) LNMO cathode materials after five cycles at 0.1C, 0.2C, 0.5C, 1C, and 2C; the first cycle charge and discharge curves of (c) MF-LNMO and (d) LNMO at various current densities;

[0031] Figure 8EIS test spectra and fitting spectra of (a) MF-LNMO and (b) LNMO positive electrodes. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] MF-LNMO(Li 1.19 Mg 0.01 Fe 0.01 Ni 0.2 Mn 0.59 O2): Lithium oxalate, manganese oxalate tetrahydrate, nickel oxalate tetrahydrate, iron acetate and magnesium oxalate dihydrate were weighed according to the molecular weight ratio, mixed and dissolved in 15 ml of pure water, and heated and stirred in a magnetic bar until the solution was clear. The lithium oxalate was in excess of 10% to make up for the lithium loss caused by the subsequent reaction; monohydrated citric acid was also dissolved in 15 ml of pure water and stirred until dissolved. After both were stirred evenly, the metal salt solution was added dropwise to the citric acid aqueous solution for chelation to form a green mixed solution, and the mixed solution was stirred at 80°C for 4h. After the sol was formed, the material was placed in a constant temperature oven at 120°C for 12h, and then the material was transferred to a muffle furnace and calcined at 850°C for 10h. After grinding, it was calcined again at 950°C for 15h, and the heating rate was 5 degrees / minute. After cooling with the furnace, the synthesized material was taken out and ground with a mortar to obtain a multi-element doped lithium-rich layered positive electrode material.

[0035] Comparative Example 1

[0036] LNMO(Li 1.2 Ni 0.2 Mn 0.6O2): Lithium oxalate, manganese oxalate tetrahydrate, nickel oxalate tetrahydrate, iron acetate and magnesium oxalate dihydrate were weighed according to the molecular weight ratio, mixed and dissolved in 15 ml of pure water, placed in a magnetic stirrer and heated until the solution was clear, wherein the lithium oxalate was in excess of 10% to compensate for the lithium loss caused by the subsequent reaction; monohydrated citric acid was also dissolved in 15 ml of pure water and stirred until dissolved. After both were stirred evenly, the metal salt solution was added dropwise to the citric acid aqueous solution for chelation to form a green mixed solution, and the mixed solution was stirred at 80°C for 4h. After the sol was formed, the material was placed in a constant temperature oven and kept at 120°C for 12h, and then the material was transferred to a muffle furnace and calcined at 950°C for 10h, with a heating rate of 5 degrees / minute, and then cooled with the furnace, the synthesized material was taken out, and the lithium-rich layered positive electrode material was obtained after grinding with a mortar.

[0037] Test Example 1: Characterization of Materials

[0038] (a) The structures of the example material MF-LNMO and the comparative example material LNMO were mainly characterized by XRD. The XRD model was a German Bruker D8 X-ray powder diffractometer. The results are shown in Figure 1 As shown, analysis of the diffraction peaks shows that the material has an R-3m space group structure; the morphology and size of the material are mainly characterized by SEM and TEM, where the SEM is a Japanese TOPCN DS-720 instrument, and the results are shown in Figure 2 As shown, it can be observed that the two materials present irregular shapes and both have some primary particle agglomeration. The particle size of MF-LNMO is slightly smaller than that of LNMO, with the former particle size between 200-400nm and the latter particle size between 300-500nm. The smaller size of the positive electrode material particles is conducive to stabilizing the cycle performance and rate performance during electrochemical testing.

[0039] (b) The spectrometer test results are as follows Figure 3 As shown, the four transition metal elements Ni, Mn and doping elements Mg and Fe in MF-LNMO are evenly distributed in the material, and the elements in the comparative example are also evenly distributed.

[0040] In summary, the sol-gel-high-temperature solid-phase sintering combined synthesis method can be used to synthesize MF-LNMO samples with small particle size and uniform distribution of elements.

[0041] Test Example 2: Electrochemical Performance Test

[0042] The battery case used for the electrochemical performance test of MF-LNMO and LNMO materials is a CR2032 button battery case set, which contains a positive electrode and a metal lithium negative electrode. The positive electrode is composed of 80% positive electrode active material, 10% conductive agent acetylene black and 10% binder PVdF. It is then evenly coated on the current collector aluminum foil and placed in a vacuum oven at 120°C for 5 hours to ensure complete removal of moisture and other organic liquids. The loading amount of active material in the electrode is 1-2 mg / cm 2 . The battery assembly was carried out in an anhydrous and oxygen-free argon glove box, where the electrolyte was 1 mol / L LiPF6 dissolved in anhydrous EC:DEC:EMC solvent. Each battery was dripped with 100 microliters of electrolyte, and the glass fiber membrane was used as the battery separator. The battery charge and discharge test was carried out on the Land BT2000 battery test system of Wuhan Blue Electric Co., Ltd., China. The test temperature was room temperature, the voltage test window was 2-4.8V, and the battery was required to stand for more than 8 hours before the test. The battery cyclic voltammetry test was tested on the CHI 660E system of Shanghai Chenhua Instrument Co., Ltd.

[0043] (1) In order to study the effect of Mg and Fe on the electrochemical performance of the original LNMO sample, we assembled lithium-ion half-cells for the modified sample MF-LNMO and the control sample LNMO and performed electrochemical tests. Cyclic voltammetry was used to explore the redox behavior of the two materials in the electrochemical behavior.

[0044] like Figure 4 As shown in the figure, during the first cycle of charging, both materials have two small peaks around 4.0V, mainly corresponding to Ni 2+ / 3+ and Ni 3+ / 4+ When the voltage exceeds 4.5V, a higher peak will appear in both, corresponding to the redox of anions. During discharge, only a reduction peak appears at about 3.75V in the first cycle, which is Ni 4+ Reduction to Ni 2+ In the subsequent cycle discharge process, a reduction peak began to appear near 3.25V. This is the Mn 4+ Reduction reaction begins to occur. For MF-LNMO, the reversibility of the next two cycles is better than that of LNMO. The redox potential difference during charge and discharge is lower than that of the comparison sample LNMO, and the polarization is smaller. MF-LNMO has a higher capacity during the first cycle of charge and discharge, which should be Fe 3+ / 3+δ The presence of redox reactions and this variable valence state endows the material with additional capacity. The peak intensity above 4.5 V for MF-LNMO is smaller than that for the control, indicating that dual doping suppresses oxygen release in the structure due to less oxygen loss during activation due to reduced metal-oxygen covalency.

[0045] (2) When LNMO materials are charged to a high voltage in the first cycle, lithium ions will be released, and irreversible release of oxygen will follow. Therefore, the first cycle coulombic efficiency of this type of material is low. Figure 5 It can be found that the introduction of Mg and Fe increases the first cycle coulomb efficiency of the material from the original 75.01% to 82.78% during electrochemical cycling, and improves the discharge specific capacity. This shows that the bonding between the transition metal and oxygen in MF-LNMO is enhanced, the irreversible redox of oxygen is suppressed, and the capacity utilization is improved.

[0046] (3) In order to explore the effect of Mg and Fe regulating the LNMO components on the cycle performance of the raw materials, we conducted constant current charge and discharge tests on MF-LNMO and LNMO at a current density of 1C (250mA / g) and a voltage range of 2-4.8V. The first-cycle discharge capacity of MF-LNMO can reach 197.9mAh / g, and the capacity retention rate can reach 85.79% after 160 cycles, while the capacity of the LNMO sample only remains at 71.29% after the same cycle. When the LNMO material is cycled, a spinel structure will gradually appear. Therefore, when the material is used as a positive electrode active material for electrochemical testing, it often shows a large voltage attenuation (i.e., a decrease in the average battery voltage). In order to study the effect of the introduction of Mg and Fe on the voltage attenuation of the original LNMO material, this work carried out cycle performance tests at 1C, such as Figure 6 As shown in the figure, after 150 cycles, MF-LNMO exhibits an average voltage drop of 0.813 mV / cycle, while the comparative LNMO exhibits a more severe voltage decay of about 2.054 mV / cycle. 2+ The doping of Fe can reduce the degree of Li / Ni cation mixing and has a stable pillar effect; 3+ The doping enhances the TM-O bond energy and stabilizes some lattice oxygen reactions.

[0047] In summary, the irreversible phase change of the MF-LNMO structure has been suppressed, its capacity retention rate has been improved, and the voltage decay has been alleviated.

[0048] (4) Rate performance of MF-LNMO and LNMO Figure 7As shown in the figure, when MF-LNMO is cycled for five cycles at rates of 0.1C, 0.2C, 0.5C, 1C, and 2C, the first cycle discharge specific capacity is 253.8, 238.8, 214, 193.8, and 173.9 mAh / g, respectively. When the current density returns to 0.1C, the discharge specific capacity can still reach 250 mAh / g. Although the comparison sample LNMO material has a higher discharge specific capacity at a low rate, its capacity drops rapidly to 147.7 mAh / g after charge and discharge cycles at various current densities, indicating that MF-LNMO has better tolerance to high current density than LNMO. Figure 7 The charge and discharge curves of the two materials at various rates are also shown.

[0049] In summary, the rate performance of MF-LNMO is better than that of LNMO, which shows that MF-LNMO has a more stable structure after component regulation, lithium ions can be more quickly inserted and deintercalated in the overall structure, the migration rate is accelerated, and the application potential is better.

[0050] (5) In order to further explore the impedance of the battery when MF-LNMO and the comparative sample LNMO are used as positive electrode materials to study their electrochemical mechanism, we performed EIS characterization on the two. Figure 8 The original spectra, fitted impedance spectra and equivalent circuits of MF-LNMO and LNMO are shown. The charge transfer resistance shown in the figure represents the resistance encountered by lithium ions when migrating in the material in a lithium-ion battery. The spectrum contains a semicircle in the mid-frequency region and a slant line in the low-frequency region, where the former refers to the charge transfer impedance (Rct) and the latter refers to the Warburg impedance of the overall material to react and diffuse. The Rct of the MF-LNMO electrode is 188.2Ω, and the resistance of the original LNMO is 337.3Ω. The charge transfer impedance of the electrode material after the introduction of Mg and Fe is smaller than that of the original LNMO electrode material, which indicates that the migration rate of lithium ions in MF-LNMO is faster and the resistance encountered is smaller.

[0051] In summary, MF-LNMO exhibits better kinetics, higher conductivity and electrochemical activity than LNMO.

[0052] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a lithium-rich layered positive electrode material for a lithium-ion battery having an average voltage drop of 0.813 mV / cycle after 150 cycles, characterized in that: The molecular formula of lithium-rich layered cathode material for lithium-ion batteries is: Li 1.19 Mg 0.01 Fe 0.01 Ni 0.2 Mn 0.59 O2; the preparation steps include: Lithium oxalate, manganese oxalate tetrahydrate, nickel oxalate tetrahydrate, ferric acetate and magnesium oxalate dihydrate were weighed according to the molecular weight ratio, mixed and dissolved in 15 ml of pure water, and heated and stirred in a magnetic nip until the solution was clear, as a metal salt solution, in which lithium oxalate was in excess of 10% to make up for the lithium loss caused by the subsequent reaction; monohydrated citric acid was also dissolved in 15 ml of pure water and stirred until dissolved. After stirring evenly, as a citric acid aqueous solution, the metal salt solution was added dropwise to the citric acid aqueous solution for chelation to form a green mixed solution, and the mixed solution was stirred at 80°C for 4h. After forming a sol, the material was placed in a constant temperature oven and kept at 120°C for 12h, and then transferred to a muffle furnace, calcined at 850°C for 10h, ground, and calcined again at 950°C for 15h, with a heating rate of 5 degrees / minute, and then cooled with the furnace, the synthesized material was taken out, and ground with a mortar to obtain a lithium-rich layered positive electrode material for lithium-ion batteries.

Citation Information

Patent Citations

  • Lithium-rich layered positive electrode material, preparation method thereof, battery positive electrode formed by lithium-rich layered positive electrode material and battery

    CN113097475A

  • Mg-doped cobalt-free lithium-rich manganese-based positive electrode material and preparation method thereof

    CN115632128A